Microsized SnS/Few‐Layer Graphene Composite with Interconnected Nanosized Building Blocks for Superior Volumetric Lithium and Sodium Storage. Issue 2 (26th September 2020) - Cheng, Deliang; Yang, Lichun; Hu, Renzong; Liu, Jiangwen; Zhu, Min
Abstract : To develop anode materials with superior volumetric storage is crucial for practical application of lithium/sodium‐ion batteries. Here, we have developed a micro/nanostructured SnS/few‐layer graphene (SnS/FLG) composite by facile scalable plasma milling. Inside the hybrid, SnS nanoparticles are tightly supported by FLG, forming nanosized primary particles as building blocks and assembling to microsized secondary granules. With this unique micro/nanostructure, the SnS/FLG composite possesses a high tap density of 1.98 g cm −3 and thus ensures a high volumetric storage. The combination of SnS nanoparticles and FLG nanosheets can not only enhance the overall electrical conductivity and facilitate the ion diffusion greatly, but alleviate the large volume expansion of SnS effectively and maintain the electrode integrity during cycling. Thus, the densely compacted SnS/FLG composite exhibits superior volumetric lithium and sodium storage, including high volumetric capacities of 1926.5/1051.4 mAh cm −3 at 0.2 A g −1, and high retained capacities of 1754.3/760.3 mAh cm −3 after 500 cycles at 1.0 A g −1 . With superior volumetric storage performance and facile scalable synthesis, the SnS/FLG composite can be a promising anode for practical batteries application. Abstract : The combination of microstructure and nanostructure enables the SnS/few‐layer graphene composite high, fast, and stable volumetric lithium/sodium storage.